2000
DOI: 10.1159/000056731
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of GBV-C/Hepatitis G Virus Viremia and Anti-E2 in Canadian Blood Donors

Abstract: Background and Objectives: GB virus C (GBV-C)/hepatitis G virus (HGV) is a recently recognized parenterally and sexually transmitted agent. The prevalence of GBV-C/HGV markers in Canadian blood donors has not been previously studied and was therefore determined. Materials and Methods: Blood donors [identity unlinked (IU), short-term temporarily deferred (STTD) and autologous groups] and donor samples with antibodies to hepatitis C (anti-HCV) or hepatitis B core were tested for GBV-C/HGV RNA and for antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In 6 studies , the samples did not include blood donors, 2 studies were carried out on commercial blood donors, and the remaining 3 did not use molecular tests for detecting HPgV‐1. We ended up including 79 studies in the systematic review . The Supplementary content table presents the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 6 studies , the samples did not include blood donors, 2 studies were carried out on commercial blood donors, and the remaining 3 did not use molecular tests for detecting HPgV‐1. We ended up including 79 studies in the systematic review . The Supplementary content table presents the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rates were reported from a wide range of countries spanning all continents. Five studies reported data from North America, 11 from South America, 21 from Europe, 33 from Asia, 5 from Africa, 2 from Australia, and 1 from both North America and Europe (we did not pool this study for results based on continent of origin). Demographic data were not consistently reported across studies, and we were not able to perform subgroup analyses based on age or gender.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] GBV-C is, in part, sexually transmitted. [39,40,41] The sex predominance of GBV-C infection is about 2:1 women:men, again similar to MS. [42] The presence of both positive (RNA genome) and negative (replication intermediate) strand flaviviral RNA in MS-6 suggests that the virus was actively replicating in the brain of this subject. Active replication is also supported by this subject's pathology report showing ''active plaques'' with a perivascular lymphocytic infiltrate (data not shown).…”
Section: Discussionmentioning
confidence: 95%